Implementation of Task-based Learning in Teaching English in Indonesia: Benefits and Problems - Sholeh, Muhammad Badrus (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
A variety of approaches exist in foreign language teaching and learning; one of them is Task-based Learning (TBL). It is an innovative approach that is developed from the Communicative Approach. The concepts of TBL have proven successful in classrooms. In this study, the writer conducted a literature review of task-based learning in teaching English dealing with the benefits and problems in the implementation of this approach in Indonesia. This paper seeks to review Task-based Learning (TBL), covering the definition of 'task' and Task-based Learning (TBL), the characteristics and stages of TBL, the teacher and students' roles in Task-based Learning, and also the advantages and disadvantages of Task-based Learning. It also addresses the application, the benefits and problems of Task-based Learning in the sense of Indonesian EFL context. This will help educators and language teachers in Indonesia to attach more importance to the contextual differences when applying Task-based Learning in Indonesia.